The ab initio study of unconventional superconductivity in CeCoIn5 and FeSe - Andrzej Ptok; Konrad J Kapcia; Przemysław Piekarz; Andrzej M Oleś (New Journal of Physics, 2017)
The electronic structure and shape of the Fermi surface are known to be of fundamental importance for the superconducting instability in real materials. We demonstrate that such an instability may be explored by static Cooper pair susceptibility renormalized by pairing interaction and present an efficient method of its evaluation using Wannier orbitals derived from ab initio calculation. As an example, this approach is used to search for an unconventional superconducting phase of the Fulde–Ferrell–Larkin–Ovchinnikov (FFLO) type in a heavy-fermion compound CeCoIn _5 and an iron-based superconductor FeSe. The results suggest that the FFLO superconducting phase occurs at finite magnetic field in both materials.